In Situ X-Ray Computed Tomography (CT) Investigation on Localized Deformation and Crack Damage Evolution in a Bimrock by Tracking Rock Blocks. (20th October 2020) - Meng, H. J.; Wang, Y.; Ren, J. Y.
Abstract : Instability of rock mass with block-in-matrix-rocks (bimrocks) often poses a threat to the geological and ecological environment; thus, investigation of the localized deformation and crack damage evolution is critical to predict the bimrock hazards. In this work, triaxial compression testing on block-in-matrix-soils (bimsoils) with a rock block percentage of 40% (mass ratio) was performed under tomographic monitoring using an original experimental setup specially designed to match the 450 kV industrial x-ray Computerized Tomography (CT) apparatus. A series of 2D CT images were obtained by carrying out CT scanning at key points throughout the test and from different positions in the sample. The physical strain localization phenomenon was well investigated using the proposed Block Tracking Movement (BTM) method to track the trajectory of rock blocks during deformation. The distribution and morphology of cracks are strongly influenced by the interactions between the rock block and the soil matrix including the repeating contact and separation between them that finally results in the macroscopic pattern of cracking. The displacement vector analysis revealed the spatial kinematics of rock blocks during sample deformation and the associated localized band evolution, which was consistent with the macroscopic crack pattern observation. The cracks corresponding to the low-density regions in the bimrock sample further indicate the inhomogeneous pattern of localized deformation. The meso-structural changes and strain localization of the bimrock under triaxial deformation are discussed first by analyzing the rock block movement using x-ray CT data.